The relation between local repolarization and T-wave morphology in heart failure patients. (15th August 2017) - Maffessanti, Francesco; Wanten, Joris; Potse, Mark; Regoli, Francois; Caputo, Maria Luce; Conte, Giulio; Sürder, Daniel; Illner, Annekatrin; Krause, Rolf; Moccetti, Tiziano; Auricchio, Angelo; Prinzen, Frits W.
Abstract: Background: Both duration and morphology of the T-wave are regarded important parameters describing repolarization of the ventricles. Conventionally, T-wave concordance is explained by an inverse relation between the time of depolarization (TD) and repolarization (TR). Little is known about T-wave morphology and TD-TR relations in patients with heart failure. Methods: Electro-anatomic maps were obtained in the left (LV) and right ventricle (RV) and in the coronary sinus (CS) in patients with heart failure with narrow (nQRS, n  = 8) and wide QRS complex with (LBBB, n  = 15) and without left bundle branch block (non-LBBB, n  = 7). TD and TR were determined from the thus acquired electrograms. Results: In nQRS and non-LBBB patients, TD-TR relations had a slope between 0 and + 1, indicating that repolarization followed the sequence of depolarization. In LBBB patients, repolarization occurred significantly earlier in the RV than in the LV, fitting with the idea that the discordant T-waves in LBBB are secondary to the abnormal depolarization sequence. However, the slopes of the TD-TR relations in the LV and CS were not significantly different from zero, indicating no major spatial gradient in LV repolarization, despite a considerable gradient in depolarization. Remarkable was also the large (~ 100 ms) transseptal gradient in repolarization. Values of the slopes of the TD-TR relation overlapped between the three patient groups, despite a difference in T-wave morphology between LBBB (all discordant) and nQRS patients (all flat/biphasic). Conclusions: Discordant T-waves in LBBB patients are explained by interventricular dispersion in repolarization. T-wave morphology is determined by more factors than the TD-TR relation alone.